Miss D & me : life with the invincible Bette Davis - Sermak, Kathryn; Morton, Danelle (New York : Hachette Books, 2017)
The legendary actress's personal assistant recounts their time together, discussing the renaissance of Davis's career in her later years and the public betrayal that nearly killed her.
Keywords: Davis, Bette, -- 1908-1989; Davis, Bette, -- 1908-1989; Motion picture actors and actresses -- United States -- Biography; Actors -- United States -- Biography